Molecular and bioinformatics characterization of fruit bromelain from ananas comosus - Tuan Norsyalieza, Tuan Aznan (2018)
Pineapple scientifically known as Ananas comosus, has several available cultivars in Malaysia, including Moris cv, N36 cv, and Sarawak cv. Bromelain has been identified as an active component and a major protease of A. comosus and has gained wide acceptance and compliance as a phototherapeutic drug. Although a considerable level of research has been devoted to bromelain from A. comosus, less attention has been paid to the fruit bromelain compared to the stem bromelain. Therefore, the purpose of this research is to reveal an in-depth information regarding fruit bromelain from A. comosus. Until recently, the three-dimensional (3D) structure of bromelain remained to be elucidated. A comprehensive information on the thorough structural organisation of bromelain is vital for therapeutic application and in the understanding of their role in cells and in other related molecular mechanisms. In this study, the screening of fruit bromelain from the local pineapple cultivars (Morris cv, N36 cv. and Sarawak cv) was implemented, followed by the isolation and cloning of the fruit bromelain from the best cultivar with the highest proteolytic activity for sequence analysis. Additionally, a comparison of the fruit and stem bromelain was performed using bioinformatics tools, including both amino acids and structural comparisons. From the screening results, the highest proteolytic activity (0.8220 U/mL) was observed from the fruit bromelain of Morris cv, followed by N36 cv (0.7695 U/mL) and Sarawak cv (0.6942 U/mL). A gene encoding for pineapple fruit bromelain was successfully isolated from Morris cv. using Reverse Transcription -Polymerase Chain Reaction (RT-PCR) techniques. The amino acid sequence and domain analysis of the fruit and stem bromelains demonstrated several differences and similarities of the cysteine protease family members. Additionally, an analysis of the modelled fruit (BAA21848) and stem (CAA08861) bromelains revealed the presence of unique properties of the predicted structures Cys-148, His-281, Gln-174 and Asn-275 are the catalytic residues of fruit bromelain whereas stem bromelain Cys-147, His-281, His-141 and Asn-302. This play crucial roles in chemical catalysis as general acid/base catalysts. The sequence analysis and structural prediction of the stem and fruit bromelain from A. comosus, along with the comparison of both structures provided a new insight on their distinct properties for industrial application. From the analysis, stem bromelain is more hydrophobic than fruit bromelain. The knowledge of the structure of these proteolytic enzymes from A. comosus is expected to increase the understanding of their functions and mechanism.